Influence of Take-up Speeds on the Structure, Properties and Dyeability of Novel Polyamide 5,6 As-spun Fibers - A. Eltahir1,, Yassir (Gezira Journal of Engineering and Applied Sciences; مجلد 14 عدد 1 (2019), 2019)
Polyamide 5,6 (PA56) as-spun fibers were successfully prepared by melt spinning process and the effects of different take-up speeds on their thermal properties, crystalline structure and dyeability were investigated by differential scanning calorimetry (DSC), wide-angle X-ray diffraction (WAXD), dynamic mechanical thermal analysis (DMTA), sonic velocity and color strength measurements. DSC results revealed that the glass transition temperature ( Tg ) of PA56 as-spun fibers increased, while the melting temperature showed no considerable variation with the take-up speed. DMTA results demonstrated that the storage modulus increased, while the peak height of tan δ decreased with take-up speeds. The equatorial (WAXD) pattern of PA56 shows α-like structure, as observed for other odd-even nylons such as nylon 5,10, nylon 9,2 and so on. It is also found that the relative crystallinity, apparent crystal sizes and molecular orientation of PA56 as-spun fibers increased with take-up speeds. As a result, the dyebath exhaustion and color strength (K/S) values decreased with the take-up speeds.